Mycogenic Metal Nanoparticles for the Treatment of Mycobacterioses - Marta Filipa Simões; Cristiane Angélica Ottoni; André Antunes (MDPI AG, 2020)
Mycobacterial infections are a resurgent and increasingly relevant problem. Within these, tuberculosis (TB) is particularly worrying as it is one of the top ten causes of death in the world and is the infectious disease that causes the highest number of deaths. A further concern is the on-going emergence of antimicrobial resistance, which seriously limits treatment. The COVID-19 pandemic has worsened current circumstances and future infections will be more incident. It is urgent to plan, draw solutions, and act to mitigate these issues, namely by exploring new approaches. The aims of this review are to showcase the extensive research and application of silver nanoparticles (AgNPs) and other metal nanoparticles (MNPs) as antimicrobial agents. We highlight the advantages of mycogenic synthesis, and report on their underexplored potential as agents in the fight against all mycobacterioses (non-tuberculous mycobacterial infections as well as TB). We propose further exploration of this field.